2017
DOI: 10.1080/14712598.2017.1346606
|View full text |Cite
|
Sign up to set email alerts
|

Treating autoimmune disorders with venom-derived peptides

Abstract: The effective treatment of autoimmune diseases remains a challenge. Voltage-gated potassium Kv1.3 channels, which are expressed in lymphocytes, are a new therapeutic target for treating autoimmune disease. Consequently, Kv1.3 channel-inhibiting venom-derived peptides are a prospective resource for new drug discovery and clinical application. Area covered: Preclinical and clinical studies have produced a wealth of information on Kv1.3 channel-inhibiting venom-derived peptides, especially from venomous scorpions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 96 publications
1
28
0
Order By: Relevance
“…Here, we found Bldesin, a pathogenic fungus‐derived antimicrobial defensin peptide with Kv1.3 channel inhibitory activity. These results from our group and Cammue et al indicated that the interaction between natural defensin peptides from different organisms and human potassium channels might be common, which suggested that natural defensins from different organisms might be an important source for the lead drug discovery targeting human potassium channels …”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Here, we found Bldesin, a pathogenic fungus‐derived antimicrobial defensin peptide with Kv1.3 channel inhibitory activity. These results from our group and Cammue et al indicated that the interaction between natural defensin peptides from different organisms and human potassium channels might be common, which suggested that natural defensins from different organisms might be an important source for the lead drug discovery targeting human potassium channels …”
Section: Discussionsupporting
confidence: 64%
“…As shown in Figure D, 1000 nM Bldesin inhibited about 40% Kv1.3 channel currents in our electrophysiological experiment system, in which 100 nM BmKTX inhibited about 80% Kv1.3 channel currents. These results indicated that pathogenic fungus‐derived defensin Bldesin has both antimicrobial and Kv1.3 channel inhibitory activities, suggesting its potential functional roles in the defense of environmental bacteria and the Kv1.3 channel‐associated host immunity …”
Section: Resultsmentioning
confidence: 90%
“…Previous studies found that in the process of T lymphocyte immune response, the voltage-gated potassium channel K V 1.3 together with calcium-activated K + channel (K Ca ) contribute to the membrane potential and calcium signaling in T cells (Shen et al . 2017 ). The up-regulated expression of K V 1.3 in T and B lymphocytes is observed during the development of autoimmune diseases (Wang et al .…”
Section: The Therapeutic Applications Of Animal Toxins In Diseasesmentioning
confidence: 99%
“…The data show that both BmKTX-D33H and ADWX-1 can effectively inhibit the activation and subsequent proliferation of human and rat CD4 + CCR7-TEM cells and the secretion of cytokines [93,94]. It is similar to the pharmacological properties of ShK-186, an anemone toxin analog that has been used in clinical research as a novel drug for the treatment of autoimmune diseases [95]. In addition, ADWX-1 can selectively inhibit the activation of effector memory T cells by inhibiting Kv1.3, thereby significantly improving the symptoms of experimental autoimmune encephalomyelitis (EAE) in a rat model [84,93].…”
Section: Anti-multiple Sclerosis and Stroke Via Kv13 41 Anti-multipmentioning
confidence: 94%